N‐Heterocyclic Carbenes and Parent Cations: Acidity, Nucleophilicity, Stability, and Hydrogen Bonding—Electrochemical Study and Ab Initio Calculations. Issue 7 (30th May 2016) - Feroci, Marta; Chiarotto, Isabella; D'Anna, Francesca; Gala, Fabrizio; Noto, Renato; Ornano, Luigi; Zollo, Giuseppe; Inesi, Achille
Abstract: N‐Heterocyclic carbenes (NHCs) are widely used as organocatalysts. Their reactivity (and instability) is related to their basicity and nucleophilicity, which, in turn, are linked to their scaffold. NHCs can be generated by chemical deprotonation or electrochemical reduction of the parent azolium cations, NHCH + s. Cyclic voltammetry enabled the reduction potential of the NHCH + s to be determined; the reduction potential is related to the acidity of the NHCH + s and the oxidation potential of the NHCs, which is related to the nucleophilicity of the NHCs. It was thus possible to order different NHCH + s and NHCs by their acidity and nucleophilicity, respectively. A study on the stability of NHCs was also performed in the absence and in the presence of acetic acid to assess the possibility of the coexistence of NHC and an acid in the same solution, opening the possibility of co‐catalysis. Finally, ab initio calculations confirmed the presence, in DMF, of hydrogen‐bonded NHCH + –NHC adducts, which could influence catalyst activity. Abstract : Bene and gone : Cyclic voltammetry data can give information on the electrogenerated basicity and nucleophilicity of N‐heterocyclic carbenes, as well as the acidity of azolium cations. Moreover, ab initio calculations confirm the presence of hydrogen‐bond adducts in solution.